Pengaruh Latihan Fisik Terhadap Kebugaran Lansia Di Masa Pandemi Covid 19 - Dwi Yuningsih; Setyaningrum Wulandari; Ida Untari; Sri Handayani; Agus Hidayat (Journal Pharma Saintika, 2020)
Background: Physical exercise for the elderly is a planned, structured, and repetitive physical activity to improve or maintain body fitness. The purpose of the study: to determine the effect of physical exercise on elderly fitness during the COVID-19 pandemic at the posyandu for the elderly, Malangjiwan village. Research method: correlation research with quantitative approach, pre-experimental design with one group pretest-posttest design model, sampling using purposive sampling technique, data analysis used is Wilcoxson test. The results of the study: the non-parametric test got a p-value of 0.000, because the p-value (0.000) (0.050) then Ha was accepted. Conclusion: there is an effect of physical exercise on the fitness of the elderly at posyandu Malangjiwan during the Covid 19 pandemic, before physical exercise as many as 17 respondents got less (bad) results and before being given physical exercise as many as 12 respondents got good (good) results.